2019
DOI: 10.1108/jpbm-02-2019-2243
|View full text |Cite
|
Sign up to set email alerts
|

The role of brand innovativeness on attitudes towards new products marketed by the brand

Abstract: Purpose This paper aims to examine whether perceived brand innovativeness has a positive effect on new product evaluations, which individual variables mediate and moderate this effect and whether perceived brand innovativeness is reinforced by new product launch. Design/methodology/approach A total of 387 adults residing in France took part in a two-stage study. The two-stage research design aimed to investigate the effect of the introduction of a new product on brand perceptions. The innovation context used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…Prior studies on innovativeness draw from an exclusively manager's perspective by largely ignoring consumers’ perception of brand innovativeness (Boisvert & Khan, 2020; O'Cass et al., 2011). These few available studies, focusing on customers perception of brand innovativeness, have shown the positive effect of brand innovativeness on perceived value (Coelho et al., 2020), brand loyalty, attitude towards the brand (Hetet et al., 2019) and purchase intention (Boisvert & Khan, 2020). Despite the significance of the direct effect, however, negligible research has focused on the interaction effects of nostalgic brand positioning and brand innovativeness on positive marketing outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies on innovativeness draw from an exclusively manager's perspective by largely ignoring consumers’ perception of brand innovativeness (Boisvert & Khan, 2020; O'Cass et al., 2011). These few available studies, focusing on customers perception of brand innovativeness, have shown the positive effect of brand innovativeness on perceived value (Coelho et al., 2020), brand loyalty, attitude towards the brand (Hetet et al., 2019) and purchase intention (Boisvert & Khan, 2020). Despite the significance of the direct effect, however, negligible research has focused on the interaction effects of nostalgic brand positioning and brand innovativeness on positive marketing outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Brand innovation affects how consumers value by the brand. [19]. Brand innovation can be described as consumer-recognized corporate innovation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Innovation leads to the development of new products or services that can help a business grow and increase its market share (Srinivasan et al, 2002). Additionally, innovation can enhance a company's reputation and credibility, which can have a positive impact on consumers' perceptions of a brand and its associated products (Hetet et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Many recent studies have investigated the influence of innovativeness on consumers' behaviours. For instance, Hetet et al (2020) found that brand innovativeness positively influenced consumers' attitudes towards a new branded product and that perceived newness mediated the effect. Geng et al (2021) discovered that the innovativeness of a sharing platform positively affected consumers' trust and, in turn, inspired consumers' use intentions towards the sharing platform.…”
mentioning
confidence: 99%